Understanding Teacher Perceptions of Assistive Technology. Issue 2 (June 2020) - Lamond, Bronwyn; Cunningham, Todd
This research examined Grade 6–10 Ontario Certified Teachers' ( n = 24) perceptions of assistive technology (AT) and the factors correlated with perceived usefulness of AT. A mixed methods design that included a survey consisting of open- and closed-ended items elicited information about teachers' AT knowledge and training, their basic computer literacy, their perception of administrative support for access to and implementation of AT, the usefulness of AT, and the factors that encourage or discourage AT use in the classroom. Results of correlational analysis suggested that computer literacy and AT knowledge were significantly positively correlated with perceived usefulness of AT, and a thematic analysis further identified that training and student factors may influence AT use. Implications for preservice and professional development teacher training are discussed, given the consistency of teacher-reported need for greater training opportunities for both students and teachers.